Improved patient-reported outcomes in patients with psoriatic arthritis treated with risankizumab: analysis of the Phase 3 trial KEEPsAKE 2. Issue 2 (14th June 2022) - Ostor, Andrew J K; Soliman, Ahmed M; Papp, Kim A; Padilla, Byron; Wang, Zailong; Eldred, Ann; de Vlam, Kurt; Kivitz, Alan
Abstract : Objectives: Determine the impact of 24-week risankizumab (RZB) versus placebo (PBO) on patient-reported outcomes (PROs) in patients with psoriatic arthritis (PsA) and inadequate response to one or two biologics (Bio-IR) and/or ≥1 conventional synthetic disease-modifying antirheumatic drug (csDMARD-IR). Methods: Patients in the Phase 3 trial, KEEPsAKE 2, were randomised (1:1) to RZB 150 mg or PBO by subcutaneous injection. PROs assessed: 36-Item Short-Form Health Survey (SF-36), Functional Assessment of Chronic Illness Therapy—Fatigue (FACIT-Fatigue), Patient's Assessment of Pain by visual analogue scale (VAS), Patient's global assessment of disease activity (PtGA), EuroQoL-5 Dimension-5 Level (EQ-5D-5L) and Work Productivity and Activity Impairment—PsA (WPAI-PsA). Least squares mean change from baseline at week 24 was compared between RZB versus PBO by mixed-effects repeated regression modelling. Results: At week 24, RZB versus PBO treatment resulted in significant differences (95% CIs) in mean change from baseline in ranked secondary endpoints SF-36 physical component summary score (3.9 (2.4 to 5.3); p<0.001) and FACIT-Fatigue (2.2 (0.6 to 3.9); p=0.009) and improvements in pain (–8.1 (–12.8 to –3.5)), PtGA (–8.8 (–13.5 to –4.2)) and EQ-5D-5L index (0.08 (0.04 to 0.11)) and VAS (5.9 (1.9 to 9.8)) (all nominal p<0.01). More RZB-treated versus PBO-treated patients reported improvements from baseline at week 24 in 7 of 8 SF-36 subdomains (nominal p<0.05). At week 24, more RZB-treated versus PBO-treated patients reported improvements in 3 of 4 WPAI-PsA domains (nominal p≤0.01). Conclusion: Overall, RBZ treatment resulted in improvements in pain, fatigue, health-related quality of life and ability to perform work in Bio-IR and/or csDMARD-IR patients with PsA. Trial registration number: NCT03671148 .